Lived experiences of nurses working in the clinical setting during Covid-19, in Ekurhuleni, Gauteng Province, South Africa - Sinethemba Nyandeni; Fhumulani Mavis Mulaudzi; Rafiat Ajoke Anokwuru (International Journal of Africa Nursing Sciences, 2024)
Background: The Coronavirus 2019 (COVID-19) outbreak rose rapidly and had a strenuous impact on the healthcare systems. As the health system responded to the pandemic, there was a change in the care rendered. Additionally, as more people became infected with the virus, the number of nurses reduced resulting in prolonged working hours and increased burden of care for the remaining few nurses. This study aimed to gain an in-depth understanding of the lived experiences of nurses working in the clinical setting during the COVID-19 pandemic in Ekurhuleni, Gauteng Province. Methods: The study followed a descriptive phenomenological approach. In-depth interviews were conducted face-to-face and telephonically with thirteen professional nurses who were purposively sampled as they had nursed COVID-19 positive patients in a hospital in Ekurhuleni District, Gauteng Province, South Africa. The audio-recorded interviews were transcribed and inductively analysed using descriptive phenomenological analysis with the aid of the ATLASti Version 9 program. Findings: Four themes emerged: (1) Nurse’s social life during COVID-19 pandemic. (2) Challenges in the clinical setting during COVID-19 pandemic. (3) COVID-19 pandemic impact on patient care. (4) Nurse’s future recommendations for pandemic management. Conclusion: The results of this study indicated that professional nurses who nursed COVID-19 patients suffered psychological distress and physical burnout. Having insufficient resources, which included Personal Protective Equipment (PPE) and other equipment exposed the nurses to the possibility of contracting COVID-19. Lack of managerial support worsened poor patient care. Therefore, further studies are needed to improve the procurement of resources and disaster preparedness. Therefore, it is recommended that managerial support which includes offering of professional counselling be done routinely, regular in-service training, and nurses should be involved in decisions affecting patient care. Implications for nursing management: Managerial support to offer professional routine counselling for improvement of mental wellbeing of the nurses and acknowledge nurses’ input.